ELECTRONIC CIGARETTES AND CARDIOVASCULAR HEALTH: CURRENT EVIDENCE AND POLICY IN POLAND - Bartosz Zwoliński,; Wiktor Kubik,; Wiktor Werenkowicz,; Jan Nowak,; Agata Król,; Kacper Sukiennicki,; Wirginia Bertman,; Natalia Kołdej,; Zuzanna Kępczyńska,; Katarzyna Szewczyk,; Kamil Borysewicz,; Klaudia Romejko,; et al. (International Journal of Innovative Technologies in Social Science, 2025)
The increasing prevalence of electronic cigarette (e-cigarette) use during the past decade has generated significant concern among public health professionals. Although e-cigarettes are often marketed as safer alternatives to conventional tobacco products, emerging evidence demonstrates that aerosolized compounds produced during vaping may exert adverse effects on cardiovascular health. This review aims to summarize the current understanding of how substances released during vaping affect the cardiovascular system, with an emphasis on molecular mechanisms, clinical findings, and epidemiological data. Additionally, the paper examines the regulatory environment in Poland and compares it to broader European Union (EU) legislation. Despite the absence of combustion-related toxins, e-cigarette aerosols contain nicotine, aldehydes, volatile organic compounds, and heavy metals, all of which can induce oxidative stress, inflammation, and endothelial dysfunction. The available evidence indicates that long-term e-cigarette use is associated with increased cardiovascular risk. Therefore, comprehensive regulation, public education, and ongoing research are essential to mitigate the potential health burden associated with vaping.